PENDEKATAN LABORATORIUM DALAM IDENTIFIKASI DINI ANEMIA PADA IBU HAMIL - Meiriska, Indri putri; Anggraini, Debie (Journal of Public Health Science, 2025)
Anemia during pregnancy remains a global maternal health concern, with high prevalence particularly in developing countries. Late diagnosis contributes to increased risks of obstetric and neonatal complications. Laboratory-based approaches offer valuable opportunities for early detection and more accurate identification of anemia etiology. Objective: This review aims to explore the role of both basic hematological and specific biochemical laboratory parameters in the early identification and risk stratification of anemia in pregnant women. Methods: This literature review compiles and analyzes scientific references related to relevant laboratory examinations, including hemoglobin, red blood cell indices, serum ferritin, transferrin saturation, serum folate, vitamin B12, homocysteine, and methylmalonic acid, with interpretation adapted to the physiological context of pregnancy. Results: Hemoglobin and red cell indices assist in identifying anemia morphologically. Serum ferritin is a sensitive indicator of iron deficiency before hemoglobin levels decline. Vitamin B12 and folate measurements are essential in detecting megaloblastic anemia, while homocysteine and MMA support the diagnosis of functional deficiencies. Integrating laboratory results with gestational age, parity, and nutritional status enables more accurate risk stratification. Conclusion: Laboratory testing plays a central role in the early detection of anemia in pregnancy, enabling more timely nutritional and medical interventions. The integration of laboratory-based diagnostics into antenatal care—particularly in primary healthcare settings—is critical for preventing complications and improving maternal and fetal outcomes.